Social Values of Early Children in The Main Character of Early Childhood: Gotong Royong - Nurbaiti, Amalia; Wachid Bambang Suharto, Abdul (International Proceedings of Nusantara Raya, 2022)
This study examines the social value of the main character's fairy tales of early childhood. The purpose of this study is to find, analyze, and describe the social values ​​contained in the Tale of the Main Characters of Early Childhood: Gotong Royong. This research uses a descriptive analysis method where the focus of the research is library research. This study uses data collection documentation with the method of reading and note-taking. The data analysis technique of this research was carried out by reducing data, presenting data, verifying and drawing conclusions. The results showed that the social value of early childhood in the Tale of the Main Character of Early Childhood: Gotong Royong consists of the social value of helping, the social value of cooperation, the social value of being loyal to friends, and the social value of motivating. The social value of helping to help is related to helping people who are in trouble, whereas in this fairy tale the social value of helping is found in the stories "Dry in the Debt" and "The Pangolin Hero;" the social value of cooperation is related to working together in achieving a common goal, where in this fairy tale, the social value of cooperation is contained in the stories "Help Kudaponi", "Tamasya" and "Sharing Tasks;" the social value of loyal friends is related to maintaining a friendship with friends regardless of the situation, where in this fairy tale the social value of loyal friends is contained in the story "Star from Heaven", and the social value of motivating is related to encouraging friends in carrying out activities, where in this fairy tale the value of Social motivation is found in the story "Visit the Little Pig". From here, the fairy tale book Main Characters for Early Childhood: Gotong Royong is the right fairy tale to be read in early childhood in building children's social values.